Towards greater resilience in the drylands: trees are the key - Wagner, B.; Leeuw, Jan de; Njenga M; Iiyama, Miyuki; Jamnadass, Ramni H. (World Agroforestry Centre, 2013)
How do we – as decision makers and policy implementers – assist dryland communities to become more resilient? There is no simple answer or single solution, but there are many emerging options and good examples of successful initiatives from within eastern Africa and beyond the region. This brief offers a set of parameters to help frame new or updated policies. It is not just a rehashing of the pressing problems plaguing people living in drylands, but rather a fresh look at what approaches work best, with a specific focus on the role of trees in fostering resilient communities (see definition of the term resilience in Box 1). This brief is part of a set of communication products from a ‘write-shop’ held in Nairobi, at the World Agroforestry Centre, with backing from the UK Department for International Development.